A Preliminary Assessment of the Reliability of a Personal Weather Station for Urban Flood Monitoring in a Tropical Coastal Urban Area: A Case Study from Kendari, Indonesia - Maheng, Dikman; Bila, Salsa Cinta; Wundari, Windy; Bachrun, Ratna; Baskara, Surya; Adriati , Yolly; Nazeer, Aftab; Radhakrishnan, Mohanasundar (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
This study conducted a preliminary assessment of the PWS reliability compared to the official BMKG reference station in a tropial coastal urban area of Kendari, Indonesia, particularly for urban flood monitoring. Daily rainfall obtained from the PWS and the BMKG station were compared over February to December 2024, using rainy days where both stations recorded rainfall exceeding 10 mm on the same day. For statistical tests, there were statistical metrics implemented in this study including Pearson correlation (r), coefficient of determination (R²), mean bias error (MBE), percent bias (PBIAS), mean absolute error (MAE), and root mean square error (RMSE). The rainfall data was also compared to flood-confirmed dates. The rainfall data analysis showed that there was moderate agreement between the PWS and the BMKG (r = 0.66, R² = 0.40, MBE = 1.83 mm, PBIAS = 4.91%, MAE = 17.12 mm, RMSE = 23.87 mm). Moreover, the PWS recorded the same rainfall category as BMKG on three flood events, particularly for heavy and very heavy rainfall category. However, the PWS showed moderate rainfall category for two flood events when the BMKG recorded heavy rainfall category. This difference could be attributed to climate background of Kendari and the device environment settings. Moreover, it is suggested that the PWS can be a useful tool for urban flood monitoring, especially during large and spatially widespread rainfall events.